KAJIAN ETNOBOTANI TUMBUHAN PANGAN LIAR DAN POTENSINYA SEBAGAI SUMBER PANGAN ALTERNATIF DI DESA PULO RAYEUK, ACEH UTARA - Wahyu Nazila; Adi Bejo Suwardi (Universitas Nias Raya, 2026)
Wild edible plants represent valuable biological resources that can support food diversification and local food security. This study aimed to identify the species of wild edible plants utilized by the community of Pulo Rayeuk Village, Tanah Luas District, North Aceh Regency, document their traditional processing methods, and analyze their role as alternative food sources. The research was conducted in April 2026 using a qualitative descriptive approach. Data were collected through semi-structured interviews, field observations, and documentation involving 15 informants selected through purposive and snowball sampling techniques. The results revealed that the local community utilizes 20 species of wild edible plants belonging to 16 plant families. The family most frequently represented was Arecaceae, with three species: Metroxylon sagu, Nypa fruticans, and Arenga pinnata. The most commonly utilized plant parts were leaves and fruits, while the predominant processing methods included boiling, stir-frying, consuming as fresh vegetables (lalapan), and eating raw. Wild edible plants serve not only as alternative food sources but also contribute to food diversification, nutritional fulfillment, and household food security. However, modernization and changing dietary patterns may reduce both the utilization of these plants and the transmission of associated local knowledge to future generations.